Perbandingan Kinerja Obligasi Ritel Indonesia dengan Sukuk Ritel Indonesia Periode Tahun 2011-2015 - Agus Marimin; Ulul Azmi Mustofa; Anik Anik (Jurnal Ilmiah Ekonomi Islam, 2016)
This research is descriptive quantitative research which is conducted in 2015-2016. It aims to test the hypothesis relating to the performance comparison of retail bonds with retail Indonesian sukuk over the period 2011-2015. This study builds on the performance of that proxy in the form of coupon yield value in the Indonesian retail bond investments and returns on investments of retail Indonesian sukuk.Samples are taken in this study.  The collecting method uses the data are obtained from the annual report IDX Indonesia Bond Market Directory. The samples used are as many as 81 data. Data are analyzed by using descriptive test, normality test and different test through SPSS software version 15. The result shows that there is no significant difference between the performance of retail bonds with the performance of retail sukuk. Keywords: Indonesian Retail Bonds and Sukuk Retail Indonesia